Factors Affecting the Effectiveness of a Company's Internal Audit - Liony, Raiza; Adang, Ferry (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to obtain empirical evidence regarding the variables that affect the effectiveness of the Company's internal audit. The independent variables used in this study are the independence, competence, and experience of the auditor. The research method used is a qualitative method and library research, one of the main reasons for qualitative research is that the research is exploratory. Empirical results show that the independence, competence, and experience of the auditor affect the effectiveness of the Company's internal audit.